2021
DOI: 10.1155/2021/5552169
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fluid/Rock Interactions on Physical Character of Tight Sandstone Reservoirs during CO2 Flooding

Abstract: Structures of pore-throat and permeability alteration caused by precipitation and the dissolution of rock matrix are serious problems during CO2 flooding into reservoirs for enhanced oil recovery (EOR). Experiments were conducted under pressure boost and reduction conditions, which simulate CO2-brine scaling in different parts of the reservoir during CO2 flooding. And experiments on the dissolution and scaling of CO2-brine-rock were carried out. The results show that the pH of brine with CO2 under high pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…The total porosity, movable fluid porosity, and permeability of the cores all increased significantly, in which the immovable fluid in the small pores increased, and the immovable fluid in the mesopores decreased. Zhao and Yin conducted a CO 2 -brine rock dissolution and scaling experiment, and the pH value of the CO 2 -containing brine under high pressure was small, and no precipitate was formed. After CO 2 flooding, agglomeration and attachment of salt crystals were found in some large pores of the core.…”
Section: Influence Of Various Factorsmentioning
confidence: 99%
“…The total porosity, movable fluid porosity, and permeability of the cores all increased significantly, in which the immovable fluid in the small pores increased, and the immovable fluid in the mesopores decreased. Zhao and Yin conducted a CO 2 -brine rock dissolution and scaling experiment, and the pH value of the CO 2 -containing brine under high pressure was small, and no precipitate was formed. After CO 2 flooding, agglomeration and attachment of salt crystals were found in some large pores of the core.…”
Section: Influence Of Various Factorsmentioning
confidence: 99%
“…According to hypothesis, fines migration reduces permeability by causing formation damage (Saeedi et al 2016). As a result of mineral precipitation and fine particles migrating within the host rock pores, formation permeability decreases (Zhao and Yin 2021). There are several types of mineral fines that contribute to permeability reduction, including clay, quartz, feldspar, and carbonate as they can fill or bridge pores.…”
Section: Chemical Reaction (Dissolution-precipitation)mentioning
confidence: 99%
“…The extent of the chemical-formation interactions depends on the concentration of the propensity minerals such as carbonates and clays in the pores of the formation rock (Saeedi et al 2016). It has been found that the injection of CO 2 into a brine saturated reservoir resulted in carbonic acid formation, which in turn, react with the minerals constituting the rock's porous framework, resulting in mineral dissolution and/or precipitation (Saeedi et al 2016;Zhao and Yin 2021). These chemical reactions change the petrophysical properties of the formation rock.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that CO 2 flooding in reservoirs results in the dissolution of carbonate minerals, silicates, and feldspars. It then causes the migration and precipitation of new clay minerals. ,, The reactivity and texture of the cement are significant factors influencing the effect of CO 2 –brine water in tight sandstone. , However, the diagenesis of tight sandstone is complex, forming multiple lithofacies of the tight sandstone with different pore structures and mineral distributions. The CO 2 reacts with complex reservoir space and mineral distributions. As a result of such a reaction, different events happen along with CO 2 flooding changing the pore sizes and morphological features.…”
Section: Introductionmentioning
confidence: 99%
“… 8 , 14 , 19 The reactivity and texture of the cement are significant factors influencing the effect of CO 2 –brine water in tight sandstone. 6 , 20 22 However, the diagenesis of tight sandstone is complex, forming multiple lithofacies of the tight sandstone with different pore structures and mineral distributions. 23 25 The CO 2 reacts with complex reservoir space and mineral distributions.…”
Section: Introductionmentioning
confidence: 99%